A three year follow up of preterm infants after moderately early treatment with dexamethasone. Issue 1 (1st July 2002) - Romagnoli, C; Zecca, E; Luciano, R; Torrioli, G; Tortorolo, G
Abstract : Objective: To assess the effect of moderately early postnatal dexamethasone treatment on growth and neurodevelopmental outcome in preterm infants. Methods: Thirty preterm infants enrolled in a randomised clinical trial to investigate the effectiveness of moderately early dexamethasone administration in the treatment of chronic lung disease were routinely followed up. Fifteen babies received a total dose of 4.75 mg/kg over 14 days from the 10th day of life, and 15 babies were untreated. Five infants in each group received open label steroids to facilitate extubation later in their clinical course. Growth and neurodevelopmental outcome are reported. Results: The mean body weight, height, and head circumference as well as the number of babies with anthropometric measurements within normal range were similar in treated and untreated babies. There was no significant difference between treated and control groups with respect to incidence of cerebral palsy, major neurosensory impairment, mean intelligence quotient scores, and behavioural abnormalities. Conclusions: Postnatal dexamethasone treatment with the schedule used in this study did not impair growth and neurodevelopmental outcome in preterm infants. Data from larger trials have raised major concern that postnatal steroid treatment may increase neurodevelopmental impairment. The full extent of the risk will only be known when more trials have reported follow up data.